Analysis of the Influence of Sunlight Radiation on the Output Power of Monocrystalline Full Cell, Half-Cut Cell, and Shingled Cell Solar Panels - Ita Ayu Purnawati; I Nyoman Satya Kumara; Wayan Gede Ariastina (Journal of Social Research, 2025)
Indonesia has a huge potential for solar energy, but its utilization until 2024 only reach 573.8 MWp. The low utilization of solar energy is caused by the limited vacant land for solar power plant installations, especially in urban areas. Rooftop solar power plants are expected to increase the use of solar energy in urban areas. Choosing the right solar panels on rooftop solar is necessary to get the best performing solar panels even though they are placed on limited land. The development of cell arrangement and shape technology in solar panels has resulted in full cell, half-cut cell, and shingled cell solar panels. The weather parameter observed in this study is sunlight radiation. Direct observation was carried out for 4 days at 08.00-16.00 WIB in the Kediri Meteorological Station (BMKG Kediri), with data collection every 5 minutes. The results of the study show that sunlight radiation has a significant influence on the output power of solar panels. The determination coefficient (R2) value of sunlight radiation against solar panels is 0.60 in monocrystalline full cells, 0.65 in monocrystalline half-cut cells, and 0.66 in monocrystalline shingled cells.